The Effect of Conductor Line to Meander Line Antenna Design - Misman, D.; Salamat, I.A; Abdul Kadir, M.F; Che Rose, M.R; Mohd Shah, M.S.R; Abd Aziz, M.Z.A; Husain, M.N (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2009)
In this paper, the meander line antenna has been designed to operate at 2.4-GHz for WLAN application. Two different designs of meander line antenna are investigated, without conductor line and with conductor line. The Microwave Office software is used for simulation design process. The antenna is fabricated on a doublesided FR-4 printed circuit board using an etching technique. The design has been tested with the Advantest Network Analyzer. The comparison between simulation and measurement results for the return loss and radiation patterns were presented. A bandwidth of 152MHz and return loss of -37.7dB were obtained at frequency 2.4GHz. The gain is comparable to microstrip yagi antenna